Implementation of a Level III neonatal intensive care unit was associated with reduced NICU mortality in a resource limited public tertiary care hospital in Guyana, South America - Sara Singh; Winsome Scott; Caitlin Yeager; Madan Rambaran; Narendra C. Singh; Leif D. Nelin (Public Library of Science (PLoS), 2023)
Neonatal mortality is a significant contributor to child mortality, and there is increasing interest in low resource settings to implement neonatal intensive care practices to lower neonatal mortality. In Guyana, South America neonatal mortality remains relatively high. At Georgetown Public Hospital Corporation (GPHC), the only tertiary referral hospital in Guyana, a Level III NICU was developed starting in January, 2012 with full implementation in September, 2015. In this study, we report the association of the implementation of a Level III NICU with in-hospital neonatal survival at GPHC. Using an observational study design, available data were collected from January 1, 2015 through September 30, 2020. During the study period, there were 30,733 deliveries at GPHC and 4,467 admissions to the NICU at GPHC. There were no significant changes in the numbers of births or NICU admissions during the time of the study. The survival rate for patients admitted to the NICU was ~64% during the first 3 quarters of 2015 with most deaths were caused by sepsis or respiratory failure. By the last quarter of 2015, the NICU survival rate increased dramatically and has been sustained at ~87% (p<0.0001). The inborn mortality rate at GPHC, calculated as a percentage of all live births at GPHC, was 2.9% prior to the full implementation of the NICU and was 1.4% after the full implementation of the NICU (p<0.0001). These findings suggest that the implementation of a Level III NICU at GPHC was associated with an improvement in survival to NICU discharge in a resource limited setting.